2017
DOI: 10.1080/10437797.2017.1283269
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Class and Field: Field Instructors’ and Liaisons’ Reactions to Information About Students’ Baseline Performance Derived From Simulated Interviews

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the author manuscript from TSpace because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page. This article was made openly accessible by U of T Faculty. Please tell us how this access benefits you. Your story matters.BRIDGING C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Twenty-nine studies (56%) referred to a specific theoretical/conceptual framework or practice model that guided the research and/or teaching using simulation. Commonly cited conceptual frameworks included deliberate practice (Bond et al, 2017; Kourgiantakis, Bogo, & Sewell, 2019; Schreiber & Minarik, 2018), Kolb’s experiential learning theory (Galbraith et al, 2014; Gates & Brown, 2017; Kourgiantakis, Bogo, & Sewell, 2019; Manning et al, 2016; Youngblood, Zinkan, Tofil, & White, 2012), holistic competence (Bogo et al, 2013, 2012, 2011; Bogo, Regehr, Baird, Paterson, & LeBlanc, 2017; Katz et al, 2014; Kourgiantakis, Sewell, & Bogo, 2019; Regehr et al, 2010; Schreiber & Minarik, 2018; Tufford, Bogo, & Asakura, 2015; Tufford, Bogo, & Katz, 2017), and adult learning theories (Greeno, Ting, & Wade, 2016; Mooradian, 2008; Rogers & Welch, 2009). With respect to practice models, motivational interviewing (MI) was noted in five studies (10%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-nine studies (56%) referred to a specific theoretical/conceptual framework or practice model that guided the research and/or teaching using simulation. Commonly cited conceptual frameworks included deliberate practice (Bond et al, 2017; Kourgiantakis, Bogo, & Sewell, 2019; Schreiber & Minarik, 2018), Kolb’s experiential learning theory (Galbraith et al, 2014; Gates & Brown, 2017; Kourgiantakis, Bogo, & Sewell, 2019; Manning et al, 2016; Youngblood, Zinkan, Tofil, & White, 2012), holistic competence (Bogo et al, 2013, 2012, 2011; Bogo, Regehr, Baird, Paterson, & LeBlanc, 2017; Katz et al, 2014; Kourgiantakis, Sewell, & Bogo, 2019; Regehr et al, 2010; Schreiber & Minarik, 2018; Tufford, Bogo, & Asakura, 2015; Tufford, Bogo, & Katz, 2017), and adult learning theories (Greeno, Ting, & Wade, 2016; Mooradian, 2008; Rogers & Welch, 2009). With respect to practice models, motivational interviewing (MI) was noted in five studies (10%).…”
Section: Resultsmentioning
confidence: 99%
“…In 10 studies (19%), simulation was used to assess generalist competencies (Bogo et al, 2013, 2012, 2011; Carrillo & Thyer, 1994; Katz et al, 2014; Lu et al, 2011; Petracchi, 1999; Petracchi & Collins, 2006; Rawlings, 2012; Tufford et al, 2017). The remaining 12 studies used simulation to assess specialized competencies, including suicide risk assessment (Bogo, Regehr, Baird, Paterson, & LeBlanc, 2017; Regehr et al, 2016), social work practice with LGBQQ populations (Logie et al, 2015), depression (Gellis & Kim, 2017), child neglect (Tufford et al, 2015), practice with children and families (Scourfield et al, 2019), screening of suicide and violence (Sampson et al, 2018), risk assessment in child welfare (LeBlanc et al, 2012), domestic violence in health care (MacDonnell et al, 2016), child maltreatment (Regehr et al, 2010), substance use (Sacco et al, 2017), and children’s services (Wilkins et al, 2018). The OSCE was used in 10 of 22 studies (45%; e.g., Bogo et al, 2012; Gellis & Kim, 2017; Katz et al, 2014; Lu et al, 2011; Sampson et al, 2018; Scourfield et al, 2019; Tufford et al, 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has found that simulationbased learning is effective to develop student competence without harm to the client (Asakura & Bogo, 2021). Others have enacted simulations in order to bridge class knowledge with field education (Bogo et al, 2017). This represents an innovative approach to circumvent the issue of white students harming marginalized communities for the sake of learning.…”
Section: Field Educationmentioning
confidence: 99%